Chitosan nanofiber-based hemostatic sponge and preparation method thereof
Through the combination of chitosan nanofibers, alginates and amorphous calcium salts, a hemostatic sponge with shape memory and rapid rebound is constructed, solving the shortcomings of the existing technology in incompressible trunk bleeding and achieving efficient blood sucking and coagulation effects.
Patent Information
- Application Number
- CN202411243309.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
Existing hemostatic materials do not work well in case of incompressible trunk bleeding, especially bleeding caused by firearms or explosions. Two-dimensional materials are difficult to absorb blood adequately and trigger coagulation reactions, and the chitosan sponge has poor resilience and crosslinking agents. Adding affects hemostatic performance.
Chitosan nanofibers are used as the sponge skeleton, and the cross-linking of alginate with chitosan and introducing amorphous calcium salts to build a sponge that can be remembered in shape and rebound rapidly, increase the specific surface area, and trigger the coagulation cascade reaction. Achieve rapid blood sucking - coagulation - hemostatic.
It improves the shape memory and rebound performance of the hemostatic sponge, enhances the contact area with blood and coagulation ability, and plays the role of different hemostatic active substances in synergistically, significantly improves the hemostatic effect in the case of incompressible bleeding.
Smart Images

Figure CN119303147A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a chitosan nanofiber-based hemostatic sponge and a preparation method thereof. Background Art
[0002] Blood is a special fluid that transports gases and nutrients and is responsible for immune surveillance and hemostatic responses. In general, minor bleeding can be suppressed by the innate coagulation pathway, but excessive bleeding can lead to morbidity and even death. In recent years, there have been a large number of reports on hemostatic materials that can stop bleeding immediately and effectively. Many different types of hemostatic strategies have been adopted, including powders / particles, sponges, hydrogels, nanofibers, and gauze. For bleeding from trauma, cuts, etc., two-dimensional hemostatic materials such as zeolite-based rapid coagulants, chitin-based nanogels, and fibrin-based bandages are used to achieve hemostasis by pressing. However, for incompressible trunk bleeding caused by firearms, explosions, or sharp objects, two-dimensional materials are not effective. At this time, three-dimensional porous elastic sponges are the most suitable materials for deep wounds, especially shape memory sponges with good swelling and high hydrophilicity, because they can fill the body bleeding cavity and compress the tissue around the wound after absorbing blood.
[0003] Chitosan, as a low-cost natural polysaccharide, is widely used in clinical medicine. It is considered to be an excellent hemostatic material due to its excellent biocompatibility and antibacterial properties, as well as the electrostatic attraction of chitosan amino groups to blood cells to promote coagulation. Chitosan has a semi-crystalline sugar chain structure. The sponge material prepared by its solution has poor resilience. The added cross-linking agent generally cross-links through the amino groups of chitosan, which reduces the hemostatic performance of chitosan. The performance improvement of chitosan hemostatic sponge is mostly carried out by modifying chitosan. The combination with other materials is simply mixed together, which cannot be fully combined with blood, and it is difficult for different hemostatic active substances to play a hemostatic role at the same time. Alginate accelerates the formation of blood clots after contact with blood to achieve a hemostatic effect due to its easy water absorption and interwoven sugar chain structure, but its water-soluble nature makes it difficult to prepare a hemostatic sponge alone. It can be cross-linked and fixed when combined with calcium ions, but it will destroy its hemostatic performance. However, the presence of calcium can promote the occurrence of coagulation cascade reactions. Summary of the invention
[0004] The present invention provides a chitosan nanofiber-based hemostatic sponge, which uses chitosan nanofiber as the main material to construct the basic skeleton of the sponge, and the alginate component is cross-linked with chitosan through a cross-linking agent, and calcium is introduced in the form of an amorphous calcium salt. The above three are combined to construct a chitosan nanofiber-based hemostatic sponge with shape memory, rapid rebound, high specific surface area, triggering coagulation cascade reaction, and rapid blood absorption-coagulation-hemostasis. The present invention combines the advantages of chitosan, alginate, and calcium, and at the same time makes up for the deficiencies of each material to achieve the effect of synergistic coagulation and hemostasis, which has important research significance.
[0005] To achieve the purpose of the present invention, the present invention provides the following technical solution: a chitosan nanofiber-based hemostatic sponge, mainly made of chitosan nanofibers, alginate, amorphous calcium salt and a cross-linking agent.
[0006] In one embodiment, the chitosan nanofibers are 1 to 99 parts, the alginate is 0.1 to 50 parts, the amorphous calcium salt is 0.1 to 20 parts, and the cross-linking agent is 0.01 to 10 parts.
[0007] The chitosan nanofiber has a diameter of less than 1 μm and a length of less than 1 mm. Too large a fiber size will affect the formation of the chitosan nanofiber hemostatic sponge, and its specific surface area will be significantly reduced, thereby reducing the exposure of the amino group.
[0008] The chitosan of the chitosan nanofiber has a deacetylation degree of 75% to 95% and a medium or high viscosity. The chitosan nanofiber can be obtained by mechanically or chemically treating chitosan fibers, or by mechanically or physically treating chitosan powder.
[0009] Alginate is sodium alginate or a modified substance based on sodium alginate.
[0010] The amorphous calcium salt is amorphous calcium phosphate or amorphous calcium carbonate.
[0011] The cross-linking agent is an epoxy compound, and may be at least one of epichlorohydrin, glycerol diglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether.
[0012] Another object of the present invention is to provide a method for preparing the chitosan nanofiber-based hemostatic sponge.
[0013] To achieve the purpose of the present invention, the present invention provides the following technical scheme: a method for preparing a chitosan nanofiber-based hemostatic sponge, comprising adding an alginate solution and an amorphous calcium salt dispersion to a chitosan nanofiber dispersion, adding a crosslinking agent after mixing evenly, and freezing and drying after the crosslinking reaction is completed to obtain the sponge.
[0014] Preferably, the chitosan deacetylation degree of the chitosan nanofibers is 75% to 99%, and the chitosan viscosity is medium viscosity or high viscosity chitosan.
[0015] Preferably, the chitosan nanofibers are nanofibers obtained by mechanical or chemical treatment and having a diameter of less than 1 μm and a length of less than 1 mm.
[0016] Preferably, the solid content of the chitosan nanofiber dispersion is 1 wt% to 10 wt%.
[0017] Preferably, the alginate is sodium alginate with a concentration of 1 wt% to 10 wt%.
[0018] Preferably, the amorphous calcium salt is amorphous calcium phosphate or amorphous calcium carbonate. Amorphous calcium phosphate is obtained by the following preparation method: 11.76 g of CaCl 2 Dissolve in 1.6L of anhydrous ethanol, add 221.79mL of triethylamine (TEA), and stir at room temperature for 30 minutes. Then, add 80mL of phosphoric acid (H 3 PO 4 , ≥85%), stirred for 12 hours, centrifuged at 6000 rpm, washed with anhydrous ethanol for 3 times to remove excess TEA, and ultrasonicated in anhydrous ethanol for 10 minutes to obtain amorphous calcium phosphate. Amorphous calcium carbonate was obtained by a similar method.
[0019] In the present invention, the mass ratio of chitosan nanofiber to alginate is 1:0.1 to 1:0.5, and the mass ratio of chitosan nanofiber to amorphous calcium salt is 1:0.1 to 1:0.5.
[0020] Preferably, the crosslinking agent is an epoxy crosslinking agent, including one or more of epichlorohydrin, glycerol diglycidyl ether, trimethylolpropane triglycidyl ether and glycerol triglycidyl ether.
[0021] The cross-linking reaction condition is to cross-link at 5° C. to 50° C. for 4 to 12 hours.
[0022] The freezing temperature is -5°C to -80°C, and the drying method is freeze-drying.
[0023] Preferably, the temperature of the cross-linking reaction is room temperature, the time of the cross-linking reaction is 6 hours, and the freezing temperature is -20°C.
[0024] The chitosan nanofiber-based hemostatic sponge material provided by the present invention is obtained by cross-linking chitosan nanofibers, alginate and amorphous calcium salt through a cross-linking agent. Compared with the prior art, the present invention uses chitosan nanofibers as the main material to construct the basic skeleton of the sponge. The nanofiber structure gives the hemostatic sponge good water absorption performance and rebound performance, and greatly increases the specific surface area of the hemostatic material, so that the sponge microstructure has a large number of pores (such asFigure 1 As shown in the figure), it provides sufficient contact sites for compounding with other hemostatic adjuvants and increases the contact area with blood, platelets and blood cells, which can give full play to the role of the positive charge of amino groups in attracting negatively charged platelets and blood cells, thereby improving the hemostatic effect. Alginate is introduced into chitosan nanofibers through cross-linking with a cross-linking agent, which avoids the loss of amino groups in chitosan molecules, retains the characteristics of alginate in absorbing blood and coagulating blood, and at the same time enhances the strength of the sponge material and the ability of the hemostatic sponge to form blood clots. The introduction of amorphous calcium salts, which themselves are nanoscale amorphous structures, gives them a larger specific surface area (such as Figure 2 As shown), it reduces the contact with sodium alginate, avoids affecting the ability of sodium alginate to form blood clots, and retains its ability to trigger blood cascade reactions, which can trigger coagulation cascade reactions and accelerate hemostasis. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Microstructure of pure chitosan nanofiber sponge;
[0026] Figure 2 Scanning electron micrograph of amorphous calcium phosphate;
[0027] Figure 3 Microstructure of chitosan nanofiber-based hemostatic sponge, which contains chitosan nanofibers, sodium alginate and amorphous calcium phosphate;
[0028] Figure 4 Blood compatibility of chitosan nanofiber-based hemostatic sponge;
[0029] Figure 5 Comparison of hemostatic effects of chitosan nanofiber-based hemostatic sponges. DETAILED DESCRIPTION
[0030] The present invention provides chitosan nanofiber-based hemostatic sponge and a preparation method thereof. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and product of the present invention have been described through preferred embodiments, and those skilled in the art can modify or appropriately change and combine the methods described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0031] Unless otherwise specified, the reagents involved in the embodiments of the present invention are all commercially available products and can be purchased through commercial channels.
[0032] In the following examples, amorphous calcium phosphate was obtained by the following preparation method: 11.76 g of CaCl 2Dissolve in 1.6L of anhydrous ethanol, add 221.79mL of triethylamine, and stir at room temperature for 30 minutes. Then, add 80mL of phosphoric acid (H 3 PO 4 , ≥85%), stirred for 12 hours, centrifuged at 6000 rpm, washed with anhydrous ethanol for 3 times to remove excess TEA, and ultrasonicated in anhydrous ethanol for 10 minutes to obtain amorphous calcium phosphate. Amorphous calcium carbonate was obtained by a similar method.
[0033] Example 1
[0034] Add 100 mL of chitosan nanofiber dispersion and water to a beaker and adjust the solid content to 2 wt%. Add 20 mL of 2.5 wt% sodium alginate solution, 2 mL of ethanol dispersion containing 0.5 g of amorphous calcium phosphate, and 1 mL of epichlorohydrin to a beaker, stir for 2 hours, transfer the mixture to a 48-well cell culture plate, crosslink at room temperature for 6 hours, then freeze the plate in a -20°C refrigerator, and finally freeze-dry at -80°C to obtain a chitosan nanofiber-based hemostatic sponge (such as Figure 3 ).
[0035] Comparative Example 1
[0036] Add 100 mL of chitosan nanofiber dispersion and water to a beaker, adjust the solid content to 2 wt%, add 1 mL of epichlorohydrin, stir for 2 hours, transfer the mixture to a 48-well cell culture plate, crosslink at room temperature for 6 hours, then freeze the plate in a -20°C refrigerator, and finally freeze-dry at -80°C to obtain a sponge containing chitosan nanofibers (such as Figure 1 ).
[0037] Comparative Example 2
[0038] Add 100 mL of chitosan nanofiber dispersion and water to a beaker, adjust the solid content to 2 wt%, add 20 mL of 2.5 wt% sodium alginate solution to the beaker, add 1 mL of epichlorohydrin, stir for 2 hours, transfer the mixture to a 48-well cell culture plate, cross-link at room temperature for 6 hours, then freeze the plate in a -20°C refrigerator, and finally freeze-dry at -80°C to obtain a chitosan nanofiber composite sodium alginate sponge.
[0039] Example 2
[0040] 20 mg of each of the three materials, chitosan nanofiber sponge (CSNF), chitosan nanofiber composite sodium alginate sponge (CSNF-Alg), and chitosan nanofiber-based hemostatic sponge (CSNF-Alg-CaP), were placed in a 2 mL centrifuge tube, and two 2 mL empty tubes were taken as controls. 1 ml of anticoagulated blood was centrifuged at 2500 rpm for 5 min to obtain red blood cells, which were washed three times with PBS to purify the red blood cells and diluted to a final concentration of 5% (v / v). 0.5 mL of red blood cell suspension (5% (V / V)) was added to the 5 centrifuge tubes of the material group and the control group and gently mixed. After standing at 37°C for 3 hours, all samples were centrifuged at (2500 rpm) for 10 minutes, and then PBS was added to the centrifuge tubes containing the materials and red blood cells. Deionized water was added to one of the other two centrifuge tubes containing cells as a positive control, and PBS was added to the other as a negative control. The resulting supernatant was transferred to measure the absorbance at 545 nm to measure the blood compatibility of the hemostatic sponge. Figure 4 The results showed that the hemolysis rates of the three materials were around 0.05%, the hemolysis rates of chitosan nanofiber sponge (CSNF) and chitosan nanofiber-based hemostatic sponge (CSNF-Alg-CaP) were comparable, while the hemolysis rates of chitosan nanofiber composite sodium alginate sponge (CSNF-Alg) were higher than both.
[0041] Example 3
[0042] Chitosan nanofiber sponge (CSNF), chitosan nanofiber composite sodium alginate sponge (CSNF-Alg), chitosan nanofiber based hemostatic sponge (CSNF-Alg-CaP), the three materials were compared with the commercial chitosan hemostatic sponge and the rat tail hemostasis when no hemostatic material was added (such as Figure 5 ). Six-week-old rats were cut off at the third coccyx of the rat's tail. After waiting for 10 seconds for the blood to flow out normally, the hemostasis experiment was started. The commercially available chitosan hemostatic sponge group (CS), chitosan nanofiber sponge group (CSNF), chitosan nanofiber composite sodium alginate sponge group (CSNF-Alg) and chitosan nanofiber-based hemostatic sponge group (CSNF-Alg-CaP) were placed on the bleeding site of the rat's tail for hemostasis, and the control group (Control) without any treatment was measured when no blood flowed out.
[0043] The results are as follows:
[0044]
[0045] Example 4
[0046] Add 100 mL of chitosan nanofiber dispersion and water to a beaker and adjust the solid content to 5 wt%. Add 20 mL of 5 wt% sodium alginate solution, 4 mL of ethanol dispersion containing 1 g of amorphous calcium phosphate, and 1 mL of glycerol diglycidyl ether to a beaker, stir for 2 hours, transfer the mixture to a 48-well cell culture plate, crosslink at room temperature for 8 hours, then freeze the plate in a -20°C refrigerator, and finally freeze-dry at -80°C to obtain a chitosan nanofiber-based hemostatic sponge.
[0047] Example 5
[0048] Add 100 mL of chitosan nanofiber dispersion and water to a beaker and adjust the solid content to 10 wt%. Add 20 mL of 10 wt% sodium alginate solution, 6 mL of ethanol dispersion containing 1.5 g of amorphous calcium phosphate, and 1 mL of glycerol triglycidyl ether to a beaker, stir for 2 hours, transfer the mixture to a 48-well cell culture plate, crosslink at room temperature for 8 hours, then freeze the plate in a -20°C refrigerator, and finally freeze-dry at -80°C to obtain a chitosan nanofiber-based hemostatic sponge.
[0049] Example 6
[0050] Add 100 mL of chitosan nanofiber dispersion and water to a beaker and adjust the solid content to 1 wt%. Add 20 mL of 1 wt% sodium alginate solution, 6 mL of ethanol dispersion containing 0.5 g of amorphous calcium phosphate, and 1 mL of trimethylolpropane triglycidyl ether to a beaker, stir for 2 hours, transfer the mixture to a 48-well cell culture plate, crosslink at room temperature for 8 hours, then freeze the plate in a -20°C refrigerator, and finally freeze-dry at -80°C to obtain a chitosan nanofiber-based hemostatic sponge.
Claims
1. A chitosan nanofiber-based hemostatic sponge, characterized in that: It is mainly made of chitosan nanofibers, alginate, amorphous calcium salt and cross-linking agent.
2. The chitosan nanofiber-based hemostatic sponge according to claim 1, characterized in that: 1-99 parts of chitosan nanofibers, 0.1-50 parts of alginate, 0.1-20 parts of amorphous calcium salt, and 0.01-10 parts of a cross-linking agent.
3. The chitosan nanofiber-based hemostatic sponge according to claim 1, characterized in that: The chitosan nanofiber has a diameter less than 1 μm and a length less than 1 mm.
4. The chitosan nanofiber-based hemostatic sponge according to claim 1, characterized in that: The chitosan deacetylation degree of the chitosan nanofiber is 75% to 95%, and the viscosity is medium viscosity or high viscosity.
5. The chitosan nanofiber-based hemostatic sponge according to claim 1, characterized in that: The alginate is sodium alginate or a modified substance based on alginate; the amorphous calcium salt is amorphous calcium phosphate or amorphous calcium carbonate; and the crosslinking agent is an epoxy compound.
6. A method for preparing a chitosan nanofiber-based hemostatic sponge, characterized in that: The chitosan nanofiber dispersion is added with alginate solution and amorphous calcium salt dispersion, mixed evenly, and then a cross-linking agent is added. After the cross-linking reaction is completed, the mixture is frozen and dried to obtain the chitosan nanofiber.
7. The method for preparing the chitosan nanofiber-based hemostatic sponge according to claim 6, characterized in that: The chitosan deacetylation degree of the chitosan nanofiber is 75% to 99%, and the viscosity is medium viscosity or high viscosity chitosan.
8. The method for preparing the chitosan nanofiber-based hemostatic sponge according to claim 6, characterized in that: The chitosan nanofiber has a diameter of less than 1 μm and a length of less than 1 mm; the chitosan nanofiber dispersion has a solid content of 1 wt% to 10 wt%; the alginate solution has a concentration of 1 wt% to 10 wt%; The mass ratio of the chitosan nanofiber to alginate is 1:0.1 to 1:0.5, and the mass ratio of the chitosan nanofiber to amorphous calcium salt is 1:0.1 to 1:0.
5.
9. The method for preparing the chitosan nanofiber-based hemostatic sponge according to claim 6, characterized in that: The cross-linking reaction conditions are 5°C to 50°C for 4 to 12 hours of static cross-linking; the freezing temperature is -5°C to -80°C, and the drying method is freeze-drying.
10. The method for preparing the chitosan nanofiber-based hemostatic sponge according to claim 6, characterized in that: The temperature of the cross-linking reaction is room temperature, the time of the cross-linking reaction is 6 hours, and the freezing temperature is -20°C.
Citation Information
Cited By
Compression hemostatic sponge and preparation method thereof
CN121243451A